MOTIVASI KERJA KARYAWAN FRONT OFFICE DI KOH TIEN MING (KTM) RESORT BATAM KEPULAUAN RIAU - Lestari Jungkar Sagala; Firdaus Yusrizal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research is about work motivation of front office employee in Hotel KTM Resort Batam. This study aims to (1) to know the driving factors from outside the front office employees' self in Koh Tien Ming (KTM) Resort Batam Riau Islands.(2) to know the motivation from inside the front office employees at Koh Tien Ming (KTM) Resort Batam Kepulauan Riau.The sample in this study amounted to 6 people using the census sampling technique.This research uses quantitative descriptive method to categorize the data then compiled by using frequency. And for data collection techniques in this study using interviews and questionnaires. By using Likert scale as a measuring tool.Based on the results of research obtained on work motivation of front office employees in Koh Tien Ming (KTM) Resort Batam is high. This is proved by the total total score of intrinsic and extrinsic actors is 209 points.Keywords: Motivation, Intrinsic Factor, Extrinsic Factor.